Analysis of the Use of JKN Mobile Applications on the Effectiveness of Registration Queues at RSUD Bandung Kiwari - Agustin, Wulan Trie; Sari, Irda (MultiTech Publisher, 2024)
One of the technologies that is developing today is network technology and the internet. The rapid development of information technology has encouraged BPJS Kesehatan to carry out digital innovation by launching a digital application known as the